(untitled) (Scottish Archaeological Internet Reports, 2004)
Four pieces of pumice were found. It has been shown that the pumice was erupted from the Katla volcanic system some time before 6800 BC and after the end of the last glaciation. This rough dating is supported by radiocarbon dating from the archaeological context in which the pumice lay. One of the pieces appears to have been worked.